1966
DOI: 10.1139/b66-103
|View full text |Cite
|
Sign up to set email alerts
|

Frost Ring Formation in the Stems of Some Coniferous Species

Abstract: Seedlings of several conifer species were artificially subjected to freezing temperatures. Microscopic examination of sections, taken at intervals after the frost, revealed the way in which frost rings developed. Differentiating tracheids and xylem mother cells were killed by the frost, leaving a permanent band of underlignified and crumpled tracheids inside a band of dead cell tissue. Most of the cambial initials remained alive but developed abnormally into short irregular tracheids. Parenchyma cells prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

1975
1975
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 7 publications
1
41
0
1
Order By: Relevance
“…We computed the EPS over 30-year windows lagged by 15 years and used an EPS value of 0.85 as a threshold for the reliability of our chronologies (Wigley et al 1984). We recorded tree rings characterized by unusual wood anatomical features, e.g., low lignin content in latewood, i.e., light rings (Filion et al 1986), rows of cells collapsed because of exceptionally low temperatures, i.e., frost rings (Glerum and Farrar 1966), intra-annual density fluctuations (IADFs) (Cherubini et al 2003), and very narrow rings, i.e., negative pointer years (sensu Schweingruber et al 1990). Tree rings with unusual wood anatomical features were analyzed with a Carl Zeiss Stemi 2000-C stereomicroscope, photographed and encoded with number codes.…”
Section: Sampling and Chronology Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…We computed the EPS over 30-year windows lagged by 15 years and used an EPS value of 0.85 as a threshold for the reliability of our chronologies (Wigley et al 1984). We recorded tree rings characterized by unusual wood anatomical features, e.g., low lignin content in latewood, i.e., light rings (Filion et al 1986), rows of cells collapsed because of exceptionally low temperatures, i.e., frost rings (Glerum and Farrar 1966), intra-annual density fluctuations (IADFs) (Cherubini et al 2003), and very narrow rings, i.e., negative pointer years (sensu Schweingruber et al 1990). Tree rings with unusual wood anatomical features were analyzed with a Carl Zeiss Stemi 2000-C stereomicroscope, photographed and encoded with number codes.…”
Section: Sampling and Chronology Preparationmentioning
confidence: 99%
“…The meteorological data from years with frost rings in our chronologies showed that they occurred when there was a sudden temperature decrease in May and, in rare cases, at the beginning of June (Table 5). In order to injure the newly formed tracheids, these frost events must have happened after the start of cambial activity (Glerum and Farrar 1966;Hantemirov et al 2004). We did not study the onset of cambial activity in detail, but in analogy with other studies we expect it to start after the middle of April at xeric sites (Antonova et al 1995;Gruber et al 2010;Eilmann et al 2011) and at the beginning of May at high altitude sites (Rossi et al 2003(Rossi et al , 2008Gruber et al 2009).…”
Section: Tree-ring Features and Climate Extremesmentioning
confidence: 99%
See 1 more Smart Citation
“…Frost records can be recorded in the annual rings of tree species and are defined by Schweingruber (2007) as anatomically abnormal and ecophysiologically pathological structures resulting from frost injuries to the cambium in the xylem, with local difficulties in sap flow dynamics and normal continuity of radial and axial tracheid morphology. In general, frost rings consist of underlignified, crumpled (deformed) tracheids, collapsed cells, traumatic parenchyma cells, and abnormal tracheids (Glerum and Farrar 1966). The position of the tissue damaged by the frost within the ring is determined by the season in which the frost event occurrs, resulting in damaged rings caused by late and/or early frosts (Stöckli and Schweingruber 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators (Day and Peace 1934;Harris 1934;Kramer and Kozlowski 1960;Rhoads 1923) have pointed out that these adversities cause similar damage. However, my studies (Glerum and Farrar 1966) on the structure and development of frost rings have led me to suspect that although other adversities cause somewhat similar damage as frost, distinct differences should occur.…”
mentioning
confidence: 99%